MENGUJI POTENSI KECURANGAN PELAPORAN KEUANGAN DENGAN MENGGUNAKAN TEORI FRAUD HEXAGON - Imang Dapit Pamungkas; Sania Fatmawati Sukma (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to examine the effect of Financial Target, Financial Stability, External Pressure, Ineffective Monitoring, Auditor Switching, Change in Director, Arrogance, and Collusion on Fraudulent Financial Statements. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2018-2021 which were selected using the Purposive Sampling method so that the total sample of companies is 172. The analytical method used is Logistics Regression Analysis with SPSS 25 measuring instrument. The results of this study indicate that external pressure and arrogance have an effect on Fraudulent Financial Statements. However, Financial Target, Financial Stability, Ineffective Monitoring, Auditor Switching, Change in Director, and Collusion have no effect on Fraudulent Financial Statements.